Regional and cross-border co-operation for sustainable development of Serbia - Stojić-Karanović Edita (Međunarodni Problemi, 2007)
On its road to EU membership Serbia faces numerous challenges. Among important ones are how to solve the problems of environmental protection and sustainable management of natural resources. After defining sustainable development and its postulates, the author gives an overview of natural resources, this including land, water, air, as well as biodiversity discussing their inter-dependence. She points to the relatedness between cultural and natural resources for sustainable development giving the 'Đerdap' National Park as an example. In the author's opinion, a very effective instrument for coping with these challenges is international co-operation in the field of sustainable use of natural and cultural-historical resources, from global connections and worldwide actions, to regional interconnections and co-operation including cross-border co-operation of neighboring countries in this area.